COMPREHENSIVE ANALYSIS OF HEALTH EQUITY INITIATIVES IN PHARMACY AND OPTICAL SERVICES PROVISION - 1Hamad salem Hadi Al_Muhmedhi, 2Khalid abdullah hassan beleh, 3Majed abdullah hassan beleh, 4salem Saud saleh Alalhareth, 5Theeb shalwan owayr alyami, 6ibrahem Amar Hamad Alsalem, 7Hamad Mohammed alyami, 8Hamad hussain mohammed al salaiman, (Chelonian Research Foundation, 2022)
Health equity initiatives play a crucial role in addressing disparities in access to pharmacy and optical services. This article provides a comprehensive survey of the different wellbeing measurements utilized in pharmacy and ophthalmology administrations. Through a subjective writing survey, this study looks at the adequacy of these measures in advancing value in well- being care. Strategies incorporate information extraction, union, and factual investigation. The findings highlight the effect of well-being measures on making strides toward care, diminishing aberrations, and progressing patient results. Inquire about is displayed with pictures, tables, and charts. The dialogue investigates suggestions for arrangement, honing, and future investigation. The result highlights the significance of subsequent endeavors to advance well-being value in pharmacy and optical services. Keywords: health equity, pharmacy services, optical services, disparities, access, patient outcomes